Evaluation of bioactivities of Pistacia vera L. hull extracts as a potential antimicrobial and antioxidant natural source - Seker, Gamze; Akbas, Meltem Yesilcimen (Sage Publications Ltd, 2024)
Pistacia vera L. hull, a the major byproduct of pistachio processing, is a source of functional compounds with antioxidant and antimicrobial activities. The extraction of these natural compounds from pistachio hulls and their use instead of synthetic chemicals has gained great attention. In this work, the phytochemical contents and antioxidant and antimicrobial activities of pistachio hull ethanolic (PVE) and aqueous (PVD) extracts obtained by microwave-assisted extraction (MAE) were investigated. Gallic acid (1.9 and 1.5 mg g(-1) dw), quercetin (0.025 and 0.009 mg g(-1) dw), total phenolic (23.3 and 14.7 mg GAE g(-1) dw) and flavonoid (5.0 and 2.9 mg QE g(-1) dw) contents and antioxidant activities (SC50 0.63 and 0.56 mg mL(-1)) of PVE and PVD extracts were determined, respectively. The extracts exhibited antimicrobial effects against Enterococcus faecalis, Staphylococcus aureus, Streptococcus uberis, Bacillus cereus, and Bacillus subtilis. Minimal inhibitory concentrations (MICs, 0.8-49.0 and 9.6-82.5 mg mL(-1)) and the minimal bactericidal concentrations (MBCs, 1.3-99.1 and 15.5-150.0 mg mL(-1)) of PVE and PVD extracts were determined, respectively. Kill curves revealed that PVE and PVD extracts could inhibit the growth of bacteria. It was shown that PVE and PVD extracts could represent a good economical source of functional and bioactive compounds.
Keywords: Pistacia vera L; hull; microwave-assisted extraction; bioactive compounds; antimicrobial activity; antioxidant activity